A campanha de educação de adolescentes e adultos no Brasil e no estado do Espírito Santo (1947-1963): um projeto civilizador - Costa, Deane Monteiro Vieira (2012)
This dissertation analyzes, through a historical perspective, the first governmental initiative started in 1947 and promoted by the Ministry of Education and Health in educating youngsters and adults in urban and rural areas of Brazil and in the state of Espírito Santo. Entitled Campanha de Educação de Adolescentes e Adultos (CEAA) – Educational Campaign of Youngsters and Adults – it was a milestone in the process of elaboration of both theoretical and practical grounds for the education of youngsters and adults. With this purpose, official documents and various didactic productions elaborated by the Pedagogic Orientation Sector of CEAA of the Ministry of Education and Health are studied. These organizations, with a peacemaking approach of sanitation, patriotism, and education, proposed a civilizing process. In his book, O processocivilizador (The civilizing process), Norbert Elias analyzes the process through which western society went habit and behavioral changes, which started in the alterations in the relationships of interdependence among individuals and social groups, and therefore, in the relationships of power. In his analysis, he uses “after-school” texts distributed throughout the country by the Serviço de Educação de Adultos (Adult Education Service), targeted to students matriculated in CEAA classes that had already mastered reading. In this social figuration, therefore, the struggle against illiteracy generated stigmatization and dishonor processes of the others – the illiterate. The inferior place was declared with the type of language used in the CEAA official documents which utilized pejorative and depreciative terms and nicknames applied to the illiterate, and also the use of indicators of low expectations towards them, fact that may be noticed in the language used in the book JucaFubávisitaumacidade. In addition to that, in the book Mulheresexemplares – Ideal women - the amplification of the role of women, taking over different social functions starting in the decade of 1940 was also oriented by CEAA.The book indicated that the roles proposed by urbanization and industrialization could not compete with the role of national pride – the role of wife and housewife. The civilizing role of the working women highlighted by this “official” text helped us construct the image of “abstained” attributed to the teacher of Cachoeiro de Itapemirim, Zilma Coelho Pinto, who led the “initiative/battle” to eradicate illiteracy in her region, in the state of Espírito Santo. Her state, national, and international recognition happened after the creation of a not-for-profit organization whose main objective was to eradicate illiteracy in her municipality, the Campanha de Alfabetizaçãoe Assistência Social de Cachoeiro de Itapemirim (CAASCI) – Campaign of Assistance and Literacy of Cachoeiro de Itapemirim –, and whose conception of education was similar to the one of CEAA, presented as the “redemption” of the Brazilian man. The teenagers, youngsters, and adults that attended this organization were seen as individuals in stage of development which could be shaped in to attend to the social demands, in other words, to occupy places that were attributed to them by the natural development of society. From the reflections raised in this study, we highlight that CEAA’s proposition of literacy played an integral role in the ongoing Brazilian civilizing process, which presented schooling since the XIX century as a civilizing reference, in its interdependence limits and of the local practice correlations in under development